G20 safeguards digital economy vulnerabilities with financial sector focus - Barry Carin (Kiel Institute for the World Economy (IfW), 2017)
The G20 can ensure a secure, resilient, sustainable and responsible digital economy, especially in the financial sector, by removing vulnerabilities in Internet infrastructure, encouraging cross-border cooperation, providing guidance to telecommunications regulators and implementing norms regarding cyber-attacks.
Keywords: L86; L59; L96; O38; 330; digital economy; cyber security; global governance